Gus Dur Ideas About Modernization Of Islamic Boarding School - Diyan Dwi Nur I; Bambang Soepeno; Sri Handayani (JURNAL HISTORICA, 2018)
Gus Dur is one of the renewed figures of modernization of Islam in Indonesia, one of which which received deep attention from Gus Dur is the modernization of education within the Islamic Boarding School body which is considered to be able to compete and adapt to the changing times. The formulation of the problem to be studied is as follows; (1) what factors influenced Gus Dur's thinking about the modernization of Islamic Boarding School education ?, (2) how did Gus Dur's thinking about the modernization of Islamic Boarding School education ?, (3) how did Abdurrahman's struggle to realize his thinking about the modernization of Islamic Boarding School education ?. This study uses the sociology of knowledge, while the theory used is the theory of Hermeneutics. The result of this research is some conception about the division in the field of Islamic education that will provide progress for Islamic Boarding School education in the future.Keywords: Islamic Boarding School, Modernization of Education